The Chronicles - García, Ramón, 1967- (Book collections on Project MUSE., 2015)
"By evoking the Old Testament book referenced in the title of the collection, The Chronicles recounts distinctive aspects of a Mexican American's presence in California. Fairy tales, bible stories, and Greek myths are reinvented as the genealogy of a poet obsessed by memory and the transformations of dislocation. The Frog Prince longs to be a frog again, Sleeping Beauty doesn't know who she is, Medusa is a misunderstood femme-fatale, Bluebeard is a desired eccentric, and Marilyn Monroe wins the first annual Miss Artichoke beauty contest. Ramón García brings to life landscapes populated by misfits who find-like their mythical counterparts-a sense of belonging between the marvelous and the ordinary, memory and reality. In coming to terms with the intricacies of immigration and migration, Garci;a defamiliarizes well-known tales, rewriting enchanting and disturbing versions of stories we thought we knew."--